Specialized outpatient care for maternal and child health in PlanificaSUS areas - Guilherme Barbosa Shimocomaqui; Eliana Tiemi Masuda; Victoria Gouveia de Souza; Ana Karina de Sousa Gadelha; Ilana Eshriqui (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To describe the organization of specialized outpatient clinics, according to the Secondary Outpatient Care Unit (SOCU) model according to the health care planning (HCP) methodology. METHODS This is a descriptive and cross-sectional study, which used secondary data from the PlanificaSUS project. It was carried out in 16 outpatient clinics specialized in maternal and child care, distributed in the five Brazilian geographic regions. A structured questionnaire was used for self-assessment on the implementation of 12 parameters in two moments, in 2019 and in 2020. These parameters are related to the care, educational, and supervisory functions set out in the SOCU model. RESULTS In 2019, only 37.5% (six) of the outpatient clinics completed at least one parameter related to the care function, most frequently the multiprofessional team with interdisciplinary action (completed in 18.8% of the outpatient clinics). No parameters from the educational and supervisory functions were completed at this initial stage. In 2020, on the other hand, parameters related to the care function also showed higher frequency, higlighting the use of the same criterion by primary care teams and outpatient clinics for risk stratification (completed in 68.8% of the outpatient clinics). In the educational and supervisory functions, parameters related to the encounter between primary care teams and outpatient clinics for case management development, integrated training promotion, and close communication bond among these professionals also increased. Completion of these three parameters was identified in 25%, 25%, and 37.5% of the outpatient clinics, respectively. CONCLUSIONS The planning methodology fostered reflection and discussion about the (re)organization of the work process and contributed to changes in maternal and child health care practices within specialized outpatient care, integrated with primary health care (PHC), from the perspective of care networks. We believe that such advances enhance access and equitable care for high-risk pregnant women and children in different geographical regions of Brazil.